Implementasi Jaringan Hotspot dan Manajemen Bandwidth untuk Meningkatkan Sistem Pembelajaran di PONPES PPAI An Nahdliyah (MAPKNU) Karangploso, Kabupaten Malang - Vasti, Yana Valda Tsania; Kusmaryanto, Sigit; Mustofa, Ali (Jurnal Mahasiswa TEUB, 2025)
Wi-Fi-based hotspot networks have become the main solution for providing broad and flexible internet access, especially in environments that require shared connections, such as educational institutions. This research focuses on the design and construction of a Wi-Fi-based hotspot network at the PPAI Annahdliyah Islamic Boarding School (MAPKNU) Karangploso, Malang Regency, with the implementation of bandwidth management for even distribution of connections. The activity stages include site surveys, hardware installation, software configuration, and Quality of Service (QoS) testing. Test results show an increase in bandwidth efficiency after implementing management using Mikrotik, where throughput increased from an average of 4.5 Mbps to 9.8 Mbps, delay was reduced from 78 ms to 45 ms, and packet loss fell from 6% to 1%. This increase reflects more efficient bandwidth allocation and better connection quality for all users.Keywords – Hotspot, Bandwidth Management, QoS.